Pengaruh Penerapan Konsep Ecopreneurship Pada Mata Kuliah Kewirausahaan Terhadap Kemampuan Literasi Lingkungan Mahasiswa Pendidikan IPA ULM - Putri Ayu Aisah; Rizky Febriyani Putri; Ellyna Hafizah (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
This study aims to determine the effect of the application of the ecopreneurship concept in entrepreneurship courses on the environmental literacy skills of science education students at Lambung Mangkurat University (ULM). The type of research used in this study is a pre-experiment with a one group Pretest-Posttest design. The population in this study were all science education students at ULM with a sample of 33 science education students from the 2022 intake who were taking entrepreneurship courses determined by purposive sampling techniques. In the learning approach in this study, using a project-based learning model was carried out to integrate the principles of ecopreneurship with entrepreneurship learning. This study resulted in a significant increase in indicators of environmental knowledge (ecological), identifying environmental issues or problems, Attitudes of appreciation for the environment Responsible for the environment based on green consumerism in everyday life which includes environmental aspects. The results of the study showed that the application of the ecopreneurship concept significantly increased students' environmental literacy skills before and after the application of the ecopreneurship concept with a sig (2- tailed) of 0.000 < 0.05 and good persone correlation with a sig (2-tailed) of 0.038 and can be categorized as positively correlated data.